Development of the SAMERA Learning Model to Improve Understanding of Sexuality Concepts from an Islamic Perspective in Early Childhood - Aliati, Nina; Reza, Muhammad; Fairuzillah, Muhammad Naufal; Setyowati, Sri (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
The incidence of sexual violence in Indonesia is increasing, primarily due to children's limited understanding of sexuality. To tackle this issue, sexuality education programs in Early Childhood Education (PAUD) are crucial. This study developed the SAMERA model (Slogan, Start, Material, Exploration, Recap, End) to integrate sexuality education for young children, based on Islamic values, as many Islamic PAUD institutions do not have such programs. The research aimed to create a valid and effective SAMERA model for children aged 5 to 6 years. Using a quantitative approach and the Dick and Carey instructional design model, the study involved 21 children from TK Aisyiyah 02 Surabaya. Results indicated that the SAMERA model is both feasible and effective in enhancing children's understanding of sexuality concepts from an Islamic perspective. Validation scores were high: 89.28% from content experts, 90.38% from media experts, and 92.02% from educators. The Wilcoxon signed-rank test showed significant improvement (p < 0.05), rejecting the null hypothesis. Furthermore, the N-Gain analysis revealed a moderate improvement in understanding, with an average score of 0.35 after implementing the SAMERA model.